An examination of the ethical influences on the work of tax practitioners - Frecknall-Hughes, Jane; Moizer, Peter; Doyle, Elaine; Summers, Barbara (Springer, 2017)
As a contribution to the continuing debate about tax practitioner ethics, this paper explores the main streams of Western ethical thought that are relevant to tax practitioners’ work, most typically deontology and consequentialism (although virtue ethics and distributive justice are also considered). It then goes on to consider the impact of such ethical influences on the professional ethical codes of conduct that govern tax practitioners’ work (with specific reference to the UK and Ireland), and attempts to unravel the complex work and ethical environment of the practice of tax in terms of tax compliance and tax avoidance. The paper then examines the prior studies on tax practitioners and ethics and the type of dilemmas that practitioners face in the context of their work. The paper proceeds to examine empirically the extent to which tax practitioners take a consequentialist versus a deontological approach in their reasoning about moral dilemmas. This is carried out by an innovative use of the Defining Issues Test